2015
DOI: 10.1890/14-1178.1
|View full text |Cite
|
Sign up to set email alerts
|

Ants are less attracted to the extrafloral nectar of plants with symbiotic, nitrogen‐fixing rhizobia

Abstract: Plants simultaneously maintain mutualistic relationships with different partners that are connected through the same host, but do not interact directly. One or more participating mutualists may alter their host's phenotype, resulting in a shift in the host's ecological interactions with all other mutualists involved. Understanding the functional interplay of mutualists associated with the same host remains an important challenge in biology. Here, we show belowground nitrogen-fixing rhizobia on lima bean (Phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 43 publications
0
31
0
2
Order By: Relevance
“…However, this is not necessarily the case, as rhizobia have been shown to also affect plant defense responses directly (e.g., Thamer et al, 2011) and indirectly (Godschalx et al, 2015). The latter is illustrated by a study with potted plants placed in the field that reported positive effects of the addition of Rhizobium sp.…”
Section: The Effect Of Nitrogen-fixing Rhizobia On Aboveground Herbivmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this is not necessarily the case, as rhizobia have been shown to also affect plant defense responses directly (e.g., Thamer et al, 2011) and indirectly (Godschalx et al, 2015). The latter is illustrated by a study with potted plants placed in the field that reported positive effects of the addition of Rhizobium sp.…”
Section: The Effect Of Nitrogen-fixing Rhizobia On Aboveground Herbivmentioning
confidence: 99%
“…Ants can act as natural enemies of herbivores and this study suggests that rhizobia can interfere with this indirect plant defense mechanism. In the presence of rhizobia, cyanogenesis (a chemical defense in legumes) is increased, and this may reduce the need for the plant to produce extrafloral nectar to attract ants (Godschalx et al, 2015).…”
Section: The Effect Of Nitrogen-fixing Rhizobia On Aboveground Herbivmentioning
confidence: 99%
See 1 more Smart Citation
“…; Godschalx et al . ), so much so that most organisms interact with many different mutualists simultaneously or sequentially throughout their lives. Empirical studies have recognized that complementarity and conflict among multiple mutualist can have substantial and diverse effects on the success of organisms that cannot be detected based on pairwise studies (Champawat ; Lau & Galloway ; Ness ; Bracken et al .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Vicia faba, association with AMF reduces extrafloral nectaries, which may result in reduced protection by ants against herbivores (Laird and Addicott, 2007). Similarly, rhizobia reduce extrafloral nectar production by lima beans (Phaseolus lunatus), leading to fewer ants attracted to rhizobia associated plants (Godschalx et al, 2015). Here, the mechanistic basis underlying the tri-trophic interaction above ground appears to be a tradeoff in plant resource allocation between root mutualists and indirect defense rewards.…”
Section: Prey Localizationmentioning
confidence: 97%